I Ruminate Therefore I Violate: The Tainted Love of Anxiously Attached and Jealous Partners - Aracı-İyiaydın, Ayşegül; Toplu-Demirtaş, Ezgi; Akçabozan-Kayabol, Nazlı Büşra; Fincham, Frank D. (SAGE Publications Inc., 2020)
Anxiously attached individuals worry about the psychological availability of their partners. Their preoccupation with unmet attachment related needs is likely accompanied by ruminative thoughts, feelings of jealousy, and dating abuse perpetration. The purpose of the current study was to investigate the prevalence of gender differences in perpetrating psychological and cyber dating abuse and to explore a hypothesized serial path from anxious attachment, through rumination, and cognitive jealousy to psychological and cyber dating abuse perpetration. The sample consisted of 562 (404 women) Turkish emerging adults. The majority of the sample perpetrated at least one psychological (88.9%) and cyber (68.4%) abusive behavior over the last six months, with women perpetrating more psychological and cyber abuse. We tested a serial mediational model for each type of dating abuse, which indicated that anxious attachment was related to more rumination (brooding), cognitive jealousy, and in turn, to psychological and cyber dating abuse perpetration. We discuss the implications of our study for research, theory, and practice. © 2020 SAGE Publications.
Keywords: anxious attachment; cyber dating abuse perpetration; emerging adults; jealousy; psychological dating abuse perpetration; rumination